Water: new aspect of hydrogen bonding in the solid state. (2022) - Milovanovic´, Milan R.; Stankovic´, Ivana M.; ivkovic´, Jelena M. Zˇ; Ninkovic´, Dragan B.; Hall, Michael B.; Zaric´, Snezˇana D.
No abstract available